One versus two anterior miniscrews for correcting upper incisor overbite and angulation: a retrospective comparative study - Arturo Vela-Hernández; Laura Gutiérrez-Zubeldia; Rocío López-García; Verónica García-Sanz; Vanessa Paredes-Gallardo; José Luis Gandía-Franco; Felicidad Lasagabaster-Latorre (SpringerOpen, 2020)
Abstract Background Miniscrews are effective devices for performing upper incisor intrusion. Different mechanics can be applied depending on the treatment objectives. This study aimed to evaluate the efficacy of one or two anterior miniscrews for upper incisor correction in cases of overbite and angulation in adult patients. Methods Forty-four adults with deep overbite were divided into two groups: group 1 was treated with one miniscrew between upper central incisors and group 2 with two miniscrews between upper lateral incisors and canines. Incisor intrusion and length were measured from lateral cephalograms before treatment, after treatment and at least 12 months into retention (T0, T1 and T2). Forces were applied (90 g) from the miniscrews to the archwire using elastomeric chains. ANOVA analysis was used to determine whether differences between evaluation times were statistically significant. Results Mean root resorption was 2.15 ± 0.85 mm, which ceased after active treatment. Overbite mean correction was − 3.23 ± 1.73 mm with no statistically significant relapse. Overbite correction and incisor intrusion were significantly greater in group 2 (− 3.80 ± 1.43 versus − 2.75 ± 1.63 for OB and 8.19 ± 3.66 versus 5.69 ± 2.66 for intrusion). Resorption and overbite correction were positively related. No counterclockwise rotation of the mandibular plane was observed. Conclusions Overbite correction can be performed by means of upper incisor intrusion without rotation of the mandibular plane. Correction of upper incisor intrusion and overbite is greater in patients treated with two miniscrews. The increase in upper incisor buccal angulation is greater with one miniscrew. Root resorption is positively related to the extent of intrusion. Stability is satisfactory regardless of whether one or two miniscrews are used.